Marked increase in photoluminescence from porous Si aged in ethanol solution. (5th January 2015) - Matsumoto, Kimihisa; Nishio, Ryosuke; Nomura, Takashi; Kamiya, Kazuhide; Inada, Mitsuru; Suzuki, Shinya
Abstract: Photoluminescence properties of porous Si aged in ethanol solution and porous Si films aged in ambient air were studied. It was shown that the photoluminescence properties of porous Si strongly depend on aging time and environmental conditions. The photoluminescence intensity of porous Si dispersed in ethanol solution increases 50-fold with aging for 7 d. This increase is accompanied by increases in Si–O bond density and lifetime, indicating that the electron–hole pair is strongly confined by the formation of surface oxide thin films. The photoluminescence intensity of porous Si films decreases with aging in ambient air, suggesting that nonradiative recombination centers are formed by natural oxidation.